The Influence of Students’ Knowledge and Attitude toward Functional Foods Consumption Behavior - Afina, Siti; Retnaningsih, Retnaningsih (Journal of Consumer Sciences, 2018)
This research was to analyze the influence of students’ knowledge and attitude toward functional foods consumption behavior. This research used cross sectional study design and was conducted at Institut Pertanian Bogor, Dramaga. Samples in this research were 204 students of Institut Pertanian Bogor chosen using simple random sampling method. Data were collected by self-administered technique using questionnaires. The results showed that the average of functional foods consumption frequency was 47 times a month and the number of types consumed was seven. The results of Pearson correlation test showed that students’ allowance, attitudes, and frequency of functional foods consumption was significantly positively correlated. Factors that have significant positive effect toward consumption frequency are allowance and students’ attitude. The number of functional foods types consumed was influenced by students’ attitude.